Oil-rent Boom in Iran? - Martin Beck (German Institute of Global and Area Studies (GIGA), 2009)
The present article aims to analyze the effects of high oil prices since 2003 on Iran. The theoretical basis of the analysis is the rentier state approach, the basic element of which is that rents are at the free disposal of the rentier. Empirically, the paper examines the issue areas of foreign policy, domestic policy and economic policy. After proving that the oil price - despite fluctuations - has constantly been at a high level in the first decade of the twenty-first century, the discussion demonstrates that Iran has used the increased rent income to support a populist policy. In terms of economic policy, the regime has pursued a redistributive strategy. The country's foreign policy, particularly the ostentatiously pursued atomic program, has been very expensive since it provoked sanctions whose costs were initially balanced only by high rent income. Yet, in his first term, Ahmadinejad failed to prepare Iran for the situation that has occurred as a result of the global financial crisis: the redistributive policy of the regime has meant that an oil price below US70 or US75 now constitutes a severe challenge for the Iranian state budget. – – Öl-Boom in Iran? Der vorliegende Beitrag stellt die Frage nach den Auswirkungen des seit 2003 hohen Erdölpreises in Iran. Theoretisch basiert die Untersuchung auf dem Rentierstaats-Ansatz. Kernelement ist hierbei die freie Disponibilität der Rente für den Empfänger. Empirisch werden die Politikfelder Außenpolitik, Innenpolitik und Wirtschaftspolitik untersucht. Nachdem gezeigt ist, dass der Erdölpreis trotz aller Fluktuationen seit 2003 ununterbrochen hoch ist, wird in Bezug auf die Innenpolitik die These verfochten, dass die erhöhte Rente für eine populistische Politik eingesetzt wurde. Wirtschaftspolitisch verfolgte Ahmadinejad einen Primat der Verteilungspolitik. In der Außenpolitik fuhr das Regime, wie insbesondere das ostentativ verfolgte Atomprogramm zeigt, eine kostenträchtige, weil Sanktionen provozierende Strategie, die nur durch die hohen Erdöleinnahmen finanziert werden konnte. Ahmadinejad verfehlte es allerdings, Iran für den Fall zu rüsten, der durch die globale Finanzkrise eintrat: Obwohl der Erdölpreis auch danach noch über dem Niveau der 1990er Jahre lag, stellt ein Erdölpreis unter US 70 oder 75 Iran angesichts der hohen Kosten der redistributiven Politik vor ernsthafte haushaltspolitische Herausforderungen.
Keywords: 300; Iran; oil; rentier-state approach; domestic policy; economic policy; foreign policy; Mineralölwirtschaft; Branchenkonjunktur; Rent Seeking; Erdölpolitik; Verteilungspolitik; Außenpolitik; Iran